Mohs Micrographic Surgery for Morpheaform Type Basal Cell Carcinoma: A Case Report - Widiatmoko, Arif; Larasaty, Nanda Shaskia; Retnani, Diah Prabawati (Jurnal Kedokteran Brawijaya, 2025)
Morpheaform basal cell carcinoma (BCC) is an infiltrative and destructive type of BCC with a high recurrence, necessitating effective and minimally invasive management. Mohs Micrographic Surgery (MMS) is a treatment option for BCC with high conservation results of the entire tumor wall with minimal removal of surrounding healthy tissue, and the lowest recurrence rate compared to other treatment options.  In this study, we report a 48-year-old woman with dark spots on the left cheek area that had enlarged over the past year. Dermatological examinations showed hyperpigmentation patches with indistinct borders, irregular edges, and telangiectasis. Fine Needle Aspiration Biopsy (FNAB) confirmed BCC, and the patient underwent Mohs Micrographic Surgery (MMS) for tumor removal. The post-procedural follow-up showed a good outcome.